Preparing Graduate Students for Community Engagement in Health Services Research - Olufunmilola Abraham; Catherine Torner (University of Minnesota Libraries Publishing, 2021)
The purpose of this paper is to shed light on the importance of didactic and experiential training in community engagement for students conducting Health Services Research (HSR) in pharmacy. The incorporation of community-based learning (CBL) courses can be beneficial for graduate students because they provide an opportunity to gain important skills in stakeholder engagement and developing sustainable research partnerships. Early exposure and mentorship of graduate students through CBL courses could minimize the risk of students entering communities in their future careers with harmful tactics such as stereotypes and implicit biases. In this paper, we draw upon previous research to identify an educational gap in community preparedness. Accordingly, we developed a community-engagement course for masters and doctoral graduate students in the HSR program at the University of Wisconsin-Madison School of Pharmacy. This paper provides an example of how other graduate programs may incorporate training in community engagement within their curriculum. In addition, we summarize how CBL courses can help address foundational graduate student knowledge gaps and offer suggestions for the formation of a CBL course.